Class act eaudiobook - Craft, Jerry (2021)
New York Times bestselling author Jerry Craft returns with a companion book to New Kid, winner of the 2020 Newbery Medal, the Coretta Scott King Author Award, and the Kirkus Prize. The audiobook was a 2020 Audie Awards Finalist for Middle Grade and named an Audible Best Audiobook of the Year. This time, it's Jordan's friend Drew who takes center stage in another laugh-out-loud funny, powerful, and important story about being one of the few kids of color in a prestigious private school. Eighth grader Drew Ellis is no stranger to the saying "You have to work twice as hard to be just as good." His grandmother has reminded him his entire life. But what if he works ten times as hard and still isn't afforded the same opportunities that his privileged classmates at the Riverdale Academy Day School take for granted? To make matters worse, Drew begins to feel as if his good friend Liam might be one of those privileged kids. He wants to pretend like everything is fine, but it's hard not to withdraw, and even their mutual friend Jordan doesn't know how to keep the group together. As the pressures mount, will Drew find a way to bridge the divide so he and his friends can truly accept each other? And most important, will he finally be able to accept himself? This original full-cast audio adaptation of the graphic novel is performed by Jesus Del Orden, Nile Bullock, Guy Lockard, Robin Miles, Peyton Lusk, Marc Thompson, Rebecca Soler, Dan Bittner, January LaVoy, Phoebe Strole, Jordan Cobb, Ron Butler, A.J Beckles, Miles J. Harvey, Kim Mai Guest, Kyla Garcia, and Soneela Nankani. New Kid, the first graphic novel to win the Newbery Medal, is now joined by Jerry Craft's powerful Class Act.